2006
DOI: 10.1111/j.0909-752x.2006.00189.x
|View full text |Cite
|
Sign up to set email alerts
|

A non‐invasive method for the in vivo determination of skin antioxidant capacity (IAC‐S®)

Abstract: In view of the simplicity and reliability of the method here presented, this new technique is proposed as a possible tool for the routine evaluation of in vivo efficacy of antioxidant functional ingredients and finished products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 8 publications
1
15
0
Order By: Relevance
“…Sweat and interstitial fluid are most often referred to as analytes . In addition, some studies have shown that the stratum corneum of the human skin is a biochemically active and informative object of research ; the prospects of using washings from the human skin as an analyte have been noted .…”
Section: Introductionmentioning
confidence: 99%
“…Sweat and interstitial fluid are most often referred to as analytes . In addition, some studies have shown that the stratum corneum of the human skin is a biochemically active and informative object of research ; the prospects of using washings from the human skin as an analyte have been noted .…”
Section: Introductionmentioning
confidence: 99%
“…Skin antioxidant network protects cells against oxidative injury and prevents the production of oxidation products. When oxidative stress overwhelms the skin antioxidant capacity, the subsequent modification of the cellular redox apparatus leads to an alteration of cell homeostasis leading to degenerative processes . In the dermo‐cosmetic field, the topical application of antioxidants is often suggested as a possible strategy to prevent and modulate oxidative skin damages.…”
Section: Methodsmentioning
confidence: 99%
“…IAC intrinsic property might be of particular interest in all the processes where it presents an overproduction of ROS/reactive nitrogen species such as inflammation to prevent and modulate oxidative skin damages and to reduce oxidative stress …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The skin is constantly exposed to chemical oxidants, air pollutants and ultraviolet (UV) solar light, which is the major generator for reactive oxygen species (ROS) that induct oxidative stress 24,25 . ROS are species of oxygen which are in a more reactive state than molecular oxygen, which can be reduced to varying degrees eg: superoxide (O 2 -), primary ROS, hydrogen peroxide, (H 2 O 2 ), produced by the further reduction of oxygen.…”
Section: I23 Physiological Parameters and Metabolites Concentratedmentioning
confidence: 99%